The Skin Picking Impact Scale: Factor structure, validity and development of a short version. Issue 4 (20th May 2013) - Snorrason, Ivar; Olafsson, Ragnar P.; Flessner, Christopher A.; Keuthen, Nancy J.; Franklin, Martin E.; Woods, Douglas W.
<x xml:space="preserve">Abstract</x> In the present study, we examined the psychometric properties of the Skin Picking Impact Scale (SPIS; Keuthen, Deckersbach, Wilhelm et al., 2001), a 10 item self‐report questionnaire designed to assess the psychosocial impact of skin picking disorder (SPD). Participants were 650 individuals who met criteria for SPD in an online survey. Exploratory and confirmatory factor analyses demonstrated a unitary factor structure with high internal consistency (α = 0.94). Consequently, we constructed an abbreviated 4‐item version that retained good internal consistency (α = 0.87) and a robust factor structure. Both the short and the full versions demonstrated discriminant and convergent/concurrent validity. In conclusion, the findings indicate that both versions are psychometrically sound measures of SPD related psychosocial impact; however, some potential limitations of the full scale are discussed.